2010
DOI: 10.1039/b9nr00333a
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte and carbon nanotube multilayers made from ionic liquid solutions

Abstract: The inevitable contact of substrates with water during the traditional practice of layer-by-layer assembly (LBL) creates problems for multiple potential applications of LBL films in electronics. To resolve this issue, we demonstrate here the possibility of a LBL process using ionic liquids (ILs), which potentially eliminates corrosion and hydration processes related to aqueous media and opens additional possibilities in structural control of LBL films. ILs are also considered to be one of the best "green" proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 69 publications
0
30
0
Order By: Relevance
“…Kotov and his group fabricated PEI multilayers (branched, Mw ≈ 25,000 Da)/PSS (Mw ≈ 1 × 10 6 Da), using LBL spin-coater [33, 60]. They found that the thickness of the multilayers linearly increases with a correlation coefficient of almost unity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Kotov and his group fabricated PEI multilayers (branched, Mw ≈ 25,000 Da)/PSS (Mw ≈ 1 × 10 6 Da), using LBL spin-coater [33, 60]. They found that the thickness of the multilayers linearly increases with a correlation coefficient of almost unity.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the thickness of the multilayers linearly increases with a correlation coefficient of almost unity. They observed an average thickness per layer pair of 6.7 nm, as measured by ellipsometry, for multilayers constructed using spin-assisted LbL with polymers dissolved in water at pH 3.7, a concentration of 50 mg/mL, and using acetonitrile as rinsing solution [33]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Some recent studies also highlighted their use in inorganic synthesis, [6][7][8][9] hybridization with nanocarbons 10,11 and molecular self-assembly. [12][13][14][15] One of the advantageous features of ILs for their application in supramolecular chemistry is expressed in terms of solvent engineering, that is, the properties of ILs can be readily tuned based on their molecular structures. Traditionally, the structures and properties of amphiphilic molecular self-assembling systems have been tuned by designing the constituent molecules.…”
Section: Introductionmentioning
confidence: 99%